2016
DOI: 10.1038/srep38310
|View full text |Cite
|
Sign up to set email alerts
|

Perilipin 5 fine-tunes lipid oxidation to metabolic demand and protects against lipotoxicity in skeletal muscle

Abstract: Lipid droplets (LD) play a central role in lipid homeostasis by controlling transient fatty acid (FA) storage and release from triacylglycerols stores, while preventing high levels of cellular toxic lipids. This crucial function in oxidative tissues is altered in obesity and type 2 diabetes. Perilipin 5 (PLIN5) is a LD protein whose mechanistic and causal link with lipotoxicity and insulin resistance has raised controversies. We investigated here the physiological role of PLIN5 in skeletal muscle upon various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 47 publications
10
59
1
Order By: Relevance
“…PLIN1 protein levels are decreased in the WAT of mice on a HFD in comparison with that of animals on a normal chow diet . In skeletal muscle, two independent studies found that PLIN5 protein expression is increased in mice upon exposure to a HFD . These findings are in agreement with a study performed in human muscle biopsies, in which PLIN5 protein levels were higher in obese and diabetic patients compared to those of healthy subjects .…”
Section: Contacts Between Mitochondria and Other Organellessupporting
confidence: 86%
See 1 more Smart Citation
“…PLIN1 protein levels are decreased in the WAT of mice on a HFD in comparison with that of animals on a normal chow diet . In skeletal muscle, two independent studies found that PLIN5 protein expression is increased in mice upon exposure to a HFD . These findings are in agreement with a study performed in human muscle biopsies, in which PLIN5 protein levels were higher in obese and diabetic patients compared to those of healthy subjects .…”
Section: Contacts Between Mitochondria and Other Organellessupporting
confidence: 86%
“…Moreover, when mice overexpressing Plin5 are subjected to a HFD, they show upregulation of browning markers (Ucp1, Cidea, Adiponectin, Cebpa) in WAT, in comparison with wild-type mice. In line with these results, another study found that overexpression of PLIN5 reduces lipolysis and fatty acid oxidation and increases glycogen synthesis and glucose oxidation in human primary myotubes [220]. Nevertheless, augmented energy demand by forskolin application increases lipid oxidation in conditions of PLIN5 overexpression to a higher rate than in control myotubes.…”
Section: Metabolic Impact Of Alterations In Proteins Participating Inmentioning
confidence: 61%
“…SFN treatment did not bring about any reduction of PLIN3 induced by FA but this may be because PLIN3 is expressed mainly at the beginning of LDs maturation, at which stage PLIN3 is playing a big role in protecting LDs against lipolysis. PLIN2 is a major component of LDs in hepatocytes and PLIN5 is primarily restricted to fatty acid oxidizing tissues . In this study, the most intense expressions of PLIN2 and PLIN5 were observed from days 6 to 10 of FA treatment in hepatocytes, at a stage which is important for the maturation of LDs due to their counteraction of lipolysis.…”
Section: Discussionsupporting
confidence: 48%
“…; Laurens et al . ). Not only is the expression of the PLIN proteins important, but also their distribution across LDs.…”
Section: Introductionmentioning
confidence: 97%